The death of arts marketing: a paradigm shift from consumption to enrichment. (7th May 2019) - Walmsley, Ben
Abstract : Purpose: The purpose of this paper is to demonstrate how researchers in the field of arts marketing are gradually abandoning the traditional marketing concept in order to respond to established and emerging modes of audience engagement. Design/methodology/approach: The study is based on a comprehensive content analysis of the past three decades of journal articles related to arts marketing. Findings: The results of the content analysis highlight that a paradigm shift in arts marketing has occurred over the past two decades, from an overriding focus on neoliberal processes of consumption towards a relational, humanistic approach, which aims to enrich audiences and interrogate the wider value and impact of their arts experiences. Research limitations/implications: The logical conclusion to be derived from this paradigmatic shift is that "arts marketing" is increasingly becoming an outmoded misnomer, which suggests the need for a fundamental reassessment of the traditional arts marketing concept. Practical implications: In order to develop meaningful relationships with audiences, arts and cultural organisations should prioritise the long-term relational approaches offered by audience engagement over short-term tactical activities such as segmentation and promotion. Originality/value: The paper advocates a radical reconceptualization of the field that would replace the transactional 4P model with a relational 4E model, derived from an adoption of theories, processes and practices related to the elements of experience, exchange, environment and engagement.